2021
DOI: 10.1101/2021.03.16.21253732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A DNA methylome biosignature in alveolar macrophages from TB-exposed individuals predicts exposure to mycobacteria

Abstract: Several studies have identified biomarkers for tuberculosis (TB) diagnosis based on blood cell transcriptomics. Here, we instead studied epigenomics in the lung compartment by obtaining induced sputum from subjects included in a TB contact tracing. CD3- and HLA-DR-positive cells were isolated from the collected sputum and DNA methylome analyses performed. Unsupervised cluster analysis revealed that DNA methylomes of cells from TB-exposed individuals and controls appeared as separate clusters and the numerous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
4
2
0
Order By: Relevance
“…Furthermore, DNAm patterns may also become altered upon microbial [ 15 ] or viral infection [ 16–18 ]. In line with this, we have previously observed that immune cells of asymptomatic, tuberculosis-exposed individuals carry a lasting DNAm signature that is linked to protection against mycobacterial infection [ 19–21 ].…”
Section: Introductionsupporting
confidence: 60%
“…Furthermore, DNAm patterns may also become altered upon microbial [ 15 ] or viral infection [ 16–18 ]. In line with this, we have previously observed that immune cells of asymptomatic, tuberculosis-exposed individuals carry a lasting DNAm signature that is linked to protection against mycobacterial infection [ 19–21 ].…”
Section: Introductionsupporting
confidence: 60%
“…Hence, all individuals fulfilling inclusion criteria, consenting to participation and providing both blood and saliva samples were included in the study. However, the sample size is similar to previous studies on the effect of BCG vaccination 18, 24 , where meaningful differences in DNA methylation upon tuberculosis infection were shown. Likewise, the belonging to the different groups described above was determined after performance of the DNA methylation analyses, and hence handling, extraction and experimental procedures performed on the samples were performed in a blinded fashion.…”
Section: Methodssupporting
confidence: 78%
“…immune cell populations have been reported both in immune-related diseases and allergies (4) as well as infectious diseases (5-7). In line with this, we have observed that immune cells of asymptomatic, tuberculosis-exposed individuals carry a lasting DNAm biosignature (8-10) that is linked to protection against mycobacterial infection (8). However, epigenetic alterations can also be induced by pathogens for their own benefit (11-14).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, we recently published a study that supports the finding of a differential DNA methylation pattern that can distinguish individuals with latent TB from IGRA-negative individuals in a similar high endemic setting in Lima, Peru 46 (MedRxiv pre-print, 2021). We also recently showed that M. tuberculosis exposure-induced epigenetic reprogrammings are more profound in pulmonary immune cells as compared to PBMCs 47 (MedRxive pre-print 2021). Here, we highlight the significance of investigating pulmonary immune cells, and the value of investigating DNA methylomes in the same study subjects, longitudinally, before and after IGRA conversion.…”
Section: Discussionmentioning
confidence: 98%